Penerapan Metode PPP (Presentation, Practice, and Production) Dalam Pembelajaran Menulis Teks Deskriptif Kelas VII SMP PGRI 4 Denpasar - Oka Ribawa, I Ketut; Sosiowati, I Gusti Ayu Gde; Sri Satyawati, Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2016)
The journal aimed at finding out whether the use of presentation, practice, and production method could improve the writing skill of descriptive essay. The data were collected by observation and documentation methods by giving assignments, questionnaires, interviews, direct record and student’s descriptive essay. The data were analyzed by descriptive qualitative method. The data were presented in the table, as well as in description sentences. The main theory used in this research is the theory of learning and teaching from Doughlas Brown. The supporting theories were taken by Jeremy Harmer entitled The Practice of English Language and Teaching and English grammar theory by Yule. The results of quantitative analysis showed that the use of PPP ( presentation, practice, and production ) method could improve the writing skill of the students. It could be seen from the result of the students’ achievement test and observation analysis which improve continuously during the aplication of the model. The mean score of the students was 61.33, which was categorized intofair level. After having treatment in the first cycle, the students’ mean inprove to 76.67 categorized into good level, the second cycle, the students’ mean score improve to 81categorized to good level. This improvement was also supported by the qualitative data. The result of the qualitative analysis showed that the use of PPP ( presentation, practice and production ) method could improve the learning motivation of the students. It could be seen from the result of questionnaire analysis and interview showed that from 18 students, 65% of students admitted that they could easy to understand about the lesson after applying PPP ( presentation, practice and production ).
Keywords: writing, descriptive text, PPP (presentation, practice and production)